Effects of traditional Chinese medicines on biochemical parameters, antioxidant capacity and heat shock protein expression in rainbow trout (Oncorhynchus mykiss) under heat stress. (2nd October 2022) - Lu, Shaoxia; Xian, Ting; Wang, Di; Wang, Chang'an; Liu, Yang; Liu, Hongbai; Han, Shicheng
Abstract: This study investigated the effects of the traditional Chinese medicines (TCMs) Huoxiangzhengqi decoction (HXZQD), Xiaochaihu decoction (XCHD) and Yinchenhao decoction (YCHD) on the biochemical parameters, antioxidant capacity and heat shock protein expression in rainbow trout ( Oncorhynchus mykiss ) under heat stress. The results showed that before stress, the serum glutathione peroxidase (GSH‐Px), catalase (CAT), hepatic heat shock protein 70 (HSP70) and heat shock protein 90β (HSP90β) mRNA expression levels in the trout were increased in the TCM groups, but the serum glucose (GLU), triglyceride (TG) and cholesterol (CHO) levels were decreased. Under heat stress at 20°C, the fishfed TCMs showed significantly decreased serum TG, CHO, creatinine (CRE) and alanine transaminase (ALT) levels ( p  < 0.05) and significantly increased serum CAT levels and hepatic HSP70 and HSP90β mRNA expression ( p  < 0.05). The AST level in the HXZQD group was significantly lower than that in the other groups ( p  < 0.05). Under heat stress at 25°C, the serum GLU, TG, CHO, aspartate aminotransferase (AST) and ALT concentrations were significantly lower in all the TCM groups than in the control group ( p  < 0.05). The CRE levels in the XCHD and HXZQD groups were significantly lower than those in the control group ( p  < 0.05), and the CAT activity in the HXZQD group was significantly higher than that in the control group ( p  < 0.05). The serum GSH‐Px activity and liver HSP70 and HSP90β mRNA expression in the fishfed TCMs were significantly higher than those in the control fish ( p  < 0.05). In conclusion, dietary supplementation with these TCMs could improve the physiological response, antioxidant capacity and the expression of two HSPs. The HXZQD group showed the best resistance to heat stress.